Review of the physiotherapy service for athletes in 2018 olympic winter games - Chang, J. Y.; Lee, Y. H.; Grant, M.-E.; Lee, J. H.; You, J. S. H.; Kim, T. G.; Kong, I. D. (British Journal of Sports Medicine, 2021)
Objective This study will provide to better understand the needs for physiotherapy services during the 2018 PyeongChang Olympic Winter Games (POG) from two polyclinics. It is necessary to understand the needs and what physiotherapists do during the Olympic Winter games for first time.